Intergeneration Comparison of the Spread Pattern of Hoax - Muhammad Edy Susilo; Senja Yustitia; Subhan Afifi (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2020)
Social media is one of the fields for spreading hoaxes or fake news. This study compared the spread patterns of hoax between Generation X and Generation Z. This study used McPrenski's Generation Theory and the concepts of DeFleur and Ball-Rokeach regarding social categories theory. A survey was conducted in Sleman Regency, Yogyakarta province, and the sample size was 240. The research was held before the Indonesia General Election2019 due to the high spread of political hoaxes. The hypothesis was tested using the T-test formula. The results showed that there were differences in hoax distribution patterns between both generations. Generation X looked more active in spreading hoax compared to Generation Z. This finding confirmed the Generation Theory and the terminology of digital immigrants and digital natives. The findings can be considered positive since Generation Z, which will be more active in the future, seemed less interested in hoaxes and tended to be more digitally literate. The digital literacy movement should consider the specificities of each target group because each group has different characteristics.